Factors Influencing the Purchase Behaviour towards Consumer Goods During the Global Oil Crisis in Oman - Tangarasa Tiburtrious, Andrew Rohanaraj (2022)
This research has focused on understanding the factors that influence, Omani consumers’ purchase behaviour towards consumer goods under the global oil crisis driven scenario. The literature review helped the researcher to identify product, price, place, promotion, socio-cultural factor, value perception and price consciousness as the variables that may affect the consumer purchase behaviour towards consumer goods. The possible influence of these factors on consumer purchase behaviour were tested through nine hypotheses, using structural equation modelling technique, on the data collected through reliability and validity tested questionnaire, among the samples identified through cluster sampling method, within the target population consisted of individuals between 15 to 64 years of age. The research found ‘product’ to exert major influence on consumers’ purchase behaviour towards consumer goods followed by price, place and promotional elements. The study also found socio-cultural factor to play a mediating role on the relationship between price and consumer purchase behaviour, apart from its direct influence on consumer purchase behaviour. Value perception was also found to influence the consumer purchase behaviour, while playing mediatory role on the relationship between consumer purchase behaviour and marketing mix elements price and promotion. This study has also found price consciousness to play moderating role on the relationship between consumer purchase behaviour and marketing mix elements price, place and promotion. This study adds immense value and variety to the existing literature with focused, country specific information, while supporting the business organizations in reviewing and improving their marketing effort. This research findings could also support the retail industry by providing focused information about the factors that influence consumers’ purchase behaviour towards consumer goods. This study also extends its contribution towards policy development by providing useful inputs to the local authorities to understand the factors that influence consumer purchase behaviour and redefine their strategies to improve consumer spending, while guiding future researchers, as these findings could be used as a point of reference for future studies.